Interview with author, Dr. Laura Pérez - Ramirez, Abraham
Interview with author, Dr. Laura Pérez, Professor of Ethnic Studies at UC Berkeley on her most recent book, Eros Ideologies: Writings on Art, Sprituality, & the Decolonial.
Related with the book "Eros ideologies. Writings on art, spirituality, and the decolonial" of Laura Pérez
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice LGBTQ+; 5-Créateur.rice PANDC; _Nettoyé